Bisphenol A (BPA) and polycyclic aromatic hydrocarbons (PAHs) in the surface sediment and bivalves from Hormozgan Province coastline in the Northern Persian Gulf: A focus on source apportionment. (March 2020) - Abootalebi Jahromi, Fatemeh; Moore, Farid; Keshavarzi, Behnam; Mohebbi-Nozar, Seyedeh Laili; Mohammadi, Zargham; Sorooshian, Armin; Abbasi, Sajjad
Abstract: This study investigates Polycyclic Aromatic Hydrocarbons (PAHs) and Bisphenol-A (BPA) pollution in coastal sediments and bivalves of Hormozgan Province coastline. The results indicated that the BPA concentration in some bivalves reached up to 340.16 ng g − 1 . The mean BPA concentration in the sediment samples was also 787.01 ng g − 1 . The ∑PAHs content in sediments ranged from 14.54 to 85.00 ng g − 1, while values for bivalves ranged from 5.37 to 16.40 ng g − 1 . Individual PAH concentrations in sediments exceeded those in bivalves for which only LMW PAHs were detected. A combination of techniques including Self-Organizing Maps (SOM), Positive Matrix Factorization (PMF), and Cluster Analysis (CA) were applied and both petrogenic and pyrogenic sources were identified. The risk of PAHs in the sediments was relatively low according to the sediment quality guidelines. The health risk indices suggest that exposure to PAHs through bivalve consumption does not impose harmful health effects upon consumers. Graphical abstract: Unlabelled Image Highlights: PAHs and BPA were identified in surface sediments and bivalves in Persian Gulf. High concentration of PAHs was reported near commercial port. The main sources of PAHs are both petrogenic and pyrogenic. Low molecular weight PAHs (LMW PAHs) were generally predominant in the bivalve samples. The highest concentration of BPA was found in stations which receive municipal wastewater.